2018
DOI: 10.33084/bjop.v1i2.375
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Catechins in Sunscreen Lotion Formulation

Abstract: Skin is the outermost part of the body which is susceptible to solar radiation. Excessive radiation from ultraviolet (UV) rays can harm the skin, such as premature aging effect, erythema, and even skin cancer. Antioxidant compounds are needed to protect the skin from excessive exposure of UV rays. The antioxidant can be useful as a defense system against free radicals, ultraviolet radiation, and air pollution. One source of antioxidant from nature is Catechins. Catechins are obtained from the isolation of gamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The phenolic compounds in particular flavonoid and tannin contained in gambier extract have the potential for their sunscreen chromophore group (single-conjugated double bonds) which can absorb UV rays both UV-A and UV-B. The SPF value from the research was higher than other lotion formulas using 1% catechin gambier at which provides an SPF value of 16.0 [22]. The data showed that the gambier leaf extract with a concentration of 1% fulfilled the requirements and has the power to protect against the sun (medium/good SPF).…”
Section: Spf Lotion Valuementioning
confidence: 78%
“…The phenolic compounds in particular flavonoid and tannin contained in gambier extract have the potential for their sunscreen chromophore group (single-conjugated double bonds) which can absorb UV rays both UV-A and UV-B. The SPF value from the research was higher than other lotion formulas using 1% catechin gambier at which provides an SPF value of 16.0 [22]. The data showed that the gambier leaf extract with a concentration of 1% fulfilled the requirements and has the power to protect against the sun (medium/good SPF).…”
Section: Spf Lotion Valuementioning
confidence: 78%
“…Good serum preparations have characteristic properties according to predetermined parameters. The preparation evaluation tests included organoleptic, pH, spreadability, and viscosity tests (Kamal & Rusdi, 2018). The results of the pH test aimed to determine the safety of bangkal leaf serum preparations (Nauclea subdita leaf) when used so that they do not cause irritation to the skin (Fikayuniar et al, 2021).…”
Section: Results and Discussion Formulation And Evaluation Of Bangkal...mentioning
confidence: 99%
“…Catechins in gambir regenerate epithelial cells and stimulate angiogenesis, granulation tissue and epithelial thickness in wound. 28,31,32…”
Section: Discussionmentioning
confidence: 99%